EL NIVEL DE DESEMPLEO Y LAS TASAS DE MIGRACIÓN RURAL EXISTENTES EN LOS HOGARES DE LA CIUDAD DE LOJA Y SU INCIDENCIA EN LOS NIVELES DE INSEGURIDAD EN EL AÑO 2014 - Carabalí, Luis Antonio (2015)
The society lojana are afflicted by a big number of problems that affect the standard of living of citizens. The social problems such as unemployment, growth population not only due to the increasing of birth rate but also by the migration of people from rural areas to urban centers and insecurity in which are exposed current societies are facts that authorities have to face, it makes essential apply tools and reliable information that reflect the reality of the environment in which authorities must exercise their action for the development of effective policies to fulfill development goals and get a good living. In front of this problem he/she thought about the present investigation that takes for title" The unemployment level and the existent rates of rural migration in the homes of the city of Loja and their incidence in the levels of insecurity in the year 2014", by means of which information was procured directly of the homes lojanos that describe the local reality in which you/they develop its daily activities. For collecting information from homes was applied a survey that contains three blocks of questions addressed to get an objective. Through that was possible process the data and present the information. The general proposed objective was, to determine the incidence that you/they have the unemployment and the rural migration on the level of insecurity in the urban area of the canton Loja, by means of a descriptive study of the local reality, with the purpose of helping to improve the quality of life of lojanos. For the effect they were used the scientific method with their derivations like they are the Inductive, Deductive, Analytic and statistical method. The results demonstrate that there is a direct relationship among the unemployment, the migration and the level of insecurity that alone the one people's 28.66% that have been victims of the delinquency denounces the fact and that the rate of unemployment of the city of Loja, is among the highest in the country. Keywords: Unemployment, Migration, Insecurity, Corelation.